GNSS Receiver Bias Model for Near Real Time TEC Monitoring at Low Latitude, Thailand - Prasert Kenpankho; Samatchaya Maichuen; Prarinya Phothila; Jianfeng Zhang; Thanapon Keokhumcheng; Sontaya Ruttanaburee; Patinya Pornsopin (Annals of Geophysics, 2026)
This research proposes and investigates GNSS receiver bias modeling for near real time total electron content (TEC) monitoring across 16 multi‑frequency GNSS stations in low latitude, Thailand, from 2022‑2024. By applying a refined methodology based on Kenpankho et al. (2021) and integrating IONOLAB‑BIAS for single station bias estimation, the research corrects for satellite and receiver inter‑frequency biases to enhance TEC accuracy. Results show a consistent upward trend in TEC values, reflecting increased latitudes, seasonal ionospheric activity, and geomagnetic storms. Comparative analysis with the IRI 2020 model using correlation coefficients and RMSE reveals spatial and temporal variation, with near equatorial latitude stations showing strong alignment than upper low latitude stations. The results highlight the importance of localized GNSS‑based TEC models for improving satellite positioning accuracy in equatorial regions and highlight the limitations of global models under dynamic ionospheric conditions.
Keywords: GNSS positioning and interference; Ionosphere and magnetosphere dynamics; Soil Moisture and Remote Sensing